Control of torpedograss (Panicum repens) and Southern watergrass (Luziola fluitans) in bermudagrass turf. (August 2019) - Brown, Philip J.; Cross, Robert B.; McCarty, Lambert B.; Kerr, Robert A.
Abstract: Two species, torpedograss and Southern watergrass, are very difficult to selectively control when they invade desirable turfgrass stands. The purpose of this study was to evaluate selective control of torpedograss and Southern watergrass in 'Tifway' bermudagrass turf. Greater than 86% control of torpedograss was observed 4 wk after sequential treatment (WAST) with quinclorac, trifloxysulfuron-sodium, quinclorac and trifloxysulfuron-sodium, sulfentrazone + imazethapyr and quinclorac and trifloxysulfuron-sodium, and quinclorac and trifloxysulfuron-sodium followed by (fb) glyphosate. However, by 8 WAST, control was reduced to <36% for all treatments. Greatest Southern watergrass control was achieved 4 WAST with trifloxysulfuron-sodium (83%), and thiencarbazone-methyl + foramsulfuron + halosulfuron-methyl (75%). Limited control (<30%) was observed with other treatments. By 8 WAST, Southern watergrass control was <12% for all treatments. This study suggests that short-term control/suppression of these two species is possible; however, long-term control is limited with single-year programs. These weeds will probably require multiple applications in successive years to reduce infestations. Future research should continue to screen other herbicides, combinations, and timings for control of these and other perennial grass weeds.